Differentiation of European yellow rust subraces within the 'Warrior(-)' genetic group. - Claudia Breitkreuz; Philipp Schulz; Anne-Kristin Schmitt; Kerstin Flath; Tiphaine Vidal; Amelia Hubbard; Kostya Kanyuka; Andreas Stahl; Jens Keilwagen; Dragan Perovic (PLoS ONE)
Wheat yellow rust is one of the most destructive and rapidly evolving wheat diseases worldwide, particularly in Europe. In 2011, the previously clonal European yellow rust races were replaced by a presumably sexually derived population, characterized as the new race called 'Warrior'. This race acquired additional virulence, leading to the emergence of 'Warrior(-)' in 2013. Since 2017, Warrior(-) has undergone further diversification into subraces, named after the wheat cultivars on which they were first detected: 'Amboise', 'Benchmark' and 'Kalmar'. While none of these subraces have been directly linked to the breakdown of a specific resistance gene, they exhibit distinct infection patterns on wheat differential sets. The lack of genetic resolution required to develop reliable genetic markers for diagnosis purposes is addressed in this study. Yellow rust isolates from the 'Warrior(-)' race group were collected as part of monitoring initiatives in France, Germany, Austria, and the UK. Marker development was based on a training set of German and French isolates with known pathotypes collected between 2017 and 2021. Using genotyping-by-sequencing (GBS) and whole genome sequencing (WGS), comparisons of subraces with Fisher's exact test (case-control study) identified 14 significant single nucleotide polymorphisms (SNPs). From these, we established four functional genetic markers capable of distinguishing between the 'Amboise' and 'Benchmark' subraces, though differentiation of 'Kalmar' was not successful. These four markers were validated on two independent control groups of isolates sampled in 2021 and 2022 from the UK (n = 30) and Germany (n = 40), respectively. While subrace predictions were accurate for the German group, predictions for the UK group failed. Principal Coordinates Analysis (PCoA) of genetic distances revealed a strong origin-driven effect, further confirmed by coverage analysis of the GBS data, which demonstrated an impact on the frequency and distribution of cleavage sites. Thus, this study provides a valuable tool for future yellow rust monitoring efforts while also highlighting significant origin-dependent effects that must be considered in genetic analyses.